(untitled) (Archaeologia Adriatica, 2022)
The paper discusses 23 Ottoman coins found in 16 sites in northern Dalmatia. Chronologically, they belong to the period from the second reign of Sultan Mehmed II, the Conqueror (1444–1446 and 1451–1481) all the way to the Egyptian coin bearing the name of Sultan Abdul Hamid II (1876–1909). These numismatic finds can be assigned to one of several different phases during which they came to northern Dalmatia: pre-Ottoman, Ottoman and post-Ottoman. The first phase includes the akçes of Sultan Mehmed II and Sultan Selim I (1512–1520). The second phase involves coins from the period of Ottoman rule, which lasted a little over a century and a half in the hinterland of northern Dalmatia. The third phase is represented by mangirs of Suleiman II (1687–1691), which were brought to northern Dalmatia shortly after the end of Ottoman rule, while the Morean War (1684–1699) was still in full flow. They are followed by numismatic finds from a much later period. Two specimens are associated with historical events related to northern Dalmatia and Egypt. One was minted for Sultan Selim III (1789–1807), and the second for Sultan Abdul Hamid II (1876–1909). The first can be related to the French intervention in Egypt in 1798, and the second with refugees fleeing from Dugi Otok to El Shatt in 1944–1945.